Study Etnografi pada Proses Penetapan Harga Belis di Rote Ndao - Tukan, Viktor Maria Akbar Soratomo; Sawarjuwono, Tjiptohadi (E-Jurnal Akuntansi; Vol 30 No 9 (2020), 2020)
The purpose of this study is to uncover the process of determining the price of belis in Rote Ndao and the meaning of the price of the belis tradition. This research uses Rosenberg's self-esteem theory approach. This research is qualitative using an ethnographic approach. This study also uses data obtained from interviews and observations. The results of this study indicate that the price-setting process is not different from the accounting price-setting process, because there are a variety of different factors. Researchers find four meanings of price. First, price as a form of appreciation. Second, price is a form of bonding. Third, price is a form of thanks. Fourth, price is a form of woman's selling price. Prices are not always seen based on material and numbers. Price has a different meaning from the point of view of the Rote Ndao. Keywords: Belis; Pricing;  Meaning The Price; Ethnography.